The Impact of COVID-19 on Formal Firms in Honduras : Evidence from Monthly Tax Returns - Bachas, Pierre; Brockmeyer, Anne; Semelet, Camille (World Bank, Washington, DC, 2021)
We measure the impact of the COVID-19 (coronavirus) crisis and the resulting lockdown on formal firms in Honduras, using monthly value-added tax records for January 2018 to August 2020. Firms' revenue fell by 26 percent, or 342.6 billion lempiras (USD 14.3 billion), in real terms between March and August 2020 and the same period in 2019. Sectors subject to stricter containment measures experienced larger revenue losses. The service sector was the most severely affected, experiencing a 45 percent revenue loss. Larger firms experienced smaller revenue losses than smaller firms, even when accounting for the sectoral composition of firm-size groups. A non-negligible number of firms remained shut down until the end of available data in August 2020.